A pH-Sensing Film from Tamarind Seed Polysaccharide with Litmus Lichen Extract as an Indicator - Tieqiang Liang (Polymers, 2017)
A new pH-sensing film was developed by using tamarind seed polysaccharide (TSP) and natural dye extracted from litmus lichen (LLE). The addition of LLE from 0 to 2.5% decreased the tensile strength and elongation at break from 30.20 to 29.97 MPa and 69.73% to 60.13%, respectively, but increased the water vapor permeability from 0.399 × 10−9 to 0.434 × 10−9 g·s−1·m−1·Pa−1. The UV–Vis spectra of the litmus lichen extract (LLE) in the pH range of 4–10 showed that the color clearly changed from orange to blue. The characterization results showed that TSP interacted with LLE through hydrogen bonds. The color of the film varied from orange (pH 4.0) to blue-violet (pH 10.0). The full cream milk spoilage test indicated that the film is suitable for application in full cream milk spoilage detection. The developed pH-sensing film could be used as a promising diagnostic tool for the detection of food spoilage.